Comparison of drug-eluting balloon versus drug-eluting stent in patients with in-stent restenosis: Insight from randomized controlled trials. (20th January 2015) - Mamuti, Wahafu; Ablimit, Alimjan; Kelimu, Wumaierjiang; Rao, Fang; Jiamali, Abulimiti; Zhang, Wei; Pei, Xiaoli; Zhang, Feng
Abstract: Backgrounds: In-stent restenosis (ISR) remains an important issue even in the current drug-eluting stent (DES) era. We performed a meta-analysis to assess the clinical efficacy and safety of drug-eluting balloon (DEB) as compared with DES for the treatment of ISR. Methods: The published literature was scanned by formal searches of electronic databases from January 2005 to February 2014. All randomized controlled trials were eligible for inclusion if they compared DEB with DES in patients with ISR. Results: Prespecified criteria were met by 4 trials involving 803 patients. There was no significant difference in the primary endpoint (12-month major adverse cardiac events) between the 2 groups (risk ratio [RR] 1.04, P = 0.80). The incidence of death (RR 0.81, P = 0.62), myocardial infarction (RR 0.66, P = 0.29), and target lesion revascularization (RR 1.35, P = 0.12) in the DEB group was also similar to those in the DES group. Conclusions: This meta-analysis showed that DEB was associated with comparable clinical outcomes to DES for the treatment of ISR. DEB might be the preferred interventional strategy for patients with ISR by obviating the need of additional stent layer. Highlights: In-stent restenosis remains an important issue even in the current drug-eluting stent era. Although the superiority of the drug-eluting balloon over the conventional balloon angioplasty in treatment of in-stent restenosis had been widely demonstrated, the relative safety and efficacy of drug-eluting balloon versus drug-eluting stent remains undetermined. Drug-eluting balloon was associated with comparable clinical outcomes to drug-eluting stent for in-stent restenosis.